Catatonia as a feature of down syndrome: An under-recognised entity?. (March 2020) - Lyons, Aisling; Allen, Nicholas M.; Flanagan, Orla; Cahalane, Deirdre
Abstract: Children and adults with Down syndrome may experience unexplained neurodevelopmental regression leading to considerable diagnostic uncertainty as well as morbidity. In this study we describe a series of seven children with Down syndrome presenting with developmental regression, some of whom had lengthy periods of symptomatology and investigation prior to a final diagnosis of catatonia. While catatonia typically presents with immobility, mutism and posturing, these symptoms can often be overlooked if not recognised as catatonic phenomena. Treatment with lorazepam led to improvement in symptoms in all, eventually reversing the catatonia in some children to previous baseline function. Autistic traits were present upon retrospective analysis, a potentially under recognised co-morbidity. It is essential to recognise catatonia in children with Down syndrome, as this is an under-recognised, treatable cause of developmental regression.